(untitled) (Journal of Kathmandu Medical College, 2018)
Background: Leiomyomas are benign smooth muscle neoplasm that typically occurs from the myometrium. Most of the women with uterine leiomyoma remain asymptomatic. Various degeneration including hyaline, cystic, myxoid and red degeneration and dystrophic calcification occur in leiomyoma, among them myxoid degeneration occurs rarely. Here is a case report of 40 years with one living child and two abortions who came with complaints of feeling of heaviness and pain at lower abdomen for six months, palpable lower abdominal mass for four months and difficulty in passing urine since 15 days. Multiple fibroids with cystic degeneration were suspected in Computed Tomography scan report. The patient underwent Total Abdominal Hysterectomy with Bilateral Salphingectomy. On cut section there was a cystic area on the body of uterus containing 1. 1 liter of straw coloured fluid. Final histopathological findings concluded multiple leiomyoma with myxoid degeneration.